2019
DOI: 10.1039/c8cc07107a
|View full text |Cite
|
Sign up to set email alerts
|

The application of click chemistry for targeting quadruplex nucleic acids

Abstract: The Cu(i)-catalyzed azide and alkyne 1,3-dipolar cycloaddition (CuAAC), commonly known as the “click reaction”, has emerged as a versatile synthetic tool for targeting quadruplex nucleic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 200 publications
0
26
0
Order By: Relevance
“…As the Cu-catalyzed click reaction between azides and alkynes is a well-established method for the variable functionalization of G4-DNA ligands [52], the berberine-adenine conjugates 4a-e were synthesized by the reaction of 9-propargyladenine (2) [53] with the 9-azidoalkylberberine derivatives 3a-e [54] (Scheme 2). Although the compounds 4a-e formed as the major products in this reaction (>>50%), they were only obtained as isolated products in low to moderate yields (16-38%), mainly because of severe difficulties to completely remove the copper ions that apparently bind tightly to the compounds.…”
Section: Synthesismentioning
confidence: 99%
“…As the Cu-catalyzed click reaction between azides and alkynes is a well-established method for the variable functionalization of G4-DNA ligands [52], the berberine-adenine conjugates 4a-e were synthesized by the reaction of 9-propargyladenine (2) [53] with the 9-azidoalkylberberine derivatives 3a-e [54] (Scheme 2). Although the compounds 4a-e formed as the major products in this reaction (>>50%), they were only obtained as isolated products in low to moderate yields (16-38%), mainly because of severe difficulties to completely remove the copper ions that apparently bind tightly to the compounds.…”
Section: Synthesismentioning
confidence: 99%
“…Recently, we used 5-ethynyl-2′-deoxyuridine and direct visualization of the chromosome behavior in cell division through the azide–alkyne click reaction [ 23 ]. The click reaction has also been applied in the labeling of myoglobin, bovine serum albumin, and other proteins [ 23 , 32 , 33 , 34 ]. Next, we checked the fluorescence spectra of the click reaction product to investigate whether the 8 et dG would be used for imaging application.…”
Section: Resultsmentioning
confidence: 99%
“…Computational biological studies suggested the distribution of G4s across the genome and their prevalence in oncogene promoters . Therefore, G4s are harnessed as potential therapeutic targets by small molecules . Various small molecules have been reported to stabilize different G4 structures.…”
Section: Figurementioning
confidence: 99%
“…[2] Therefore, G4s are harnessed as potential therapeutic targets by small molecules. [3,4] Various small molecules have been reported to stabilize different G4 structures. Small molecules capable of stabilizing G4 can trigger DNA double-strand breaks and induce DNA damage response (DDR) and cell death.…”
mentioning
confidence: 99%